PENDEKATAN E-LEARNING DENGAN FASILITAS BLOG SEBAGAI MEDIA DALAM MATA KULIAH READING DAN WRITING (Lingua, 2011)
This study is a basic one. The objectives are to describe the readiness of planning and implementing theinternet-based program in English Department, to appraise student motivation and need in using the internetbasedlearning media that support their reading and writing skills in and outside the classroom, and to assessthe implementation, use and development of blog media in their reading and writing classes for one semester.The study involves the students from the reading and writing classes during the data collection by havingquestionnaires, discussion and observation to each class blog. The descriptive-qualitative approach is used withregards to quantitative outputs from the questionnaires. The study shows that the availability of internet facility inEnglish Department still needs improvement along with the extended requirements for the internet-basedlearning process, student skill in information technology and their motivation to access more quality information.Proper planning should be arranged in the learning process that uses blogs as the media, by emphasizingvalues, characters, novelty of the ideas revealed in the student writing works.Kata kunci: e-learning, media blog, jaringan internet, proses pembelajaran